Heritage planning principles and process - Kalman, Harold 1943- (New York Routledge, 2014)
"Heritage Planning : Principles and Process provides a comprehensive overview of heritage planning as an area of professional practice. The book first addresses the context and principles of heritage planning, including land-use law, planning practice, and international heritage doctrine, all set within the framework of larger societal issues such as sustainability and ethics. The book then takes readers through the pragmatic processes of heritage practice including collecting data, identifying community opinion, determining heritage significance, the best practices and methods of creating a conservation plan, and managing change"--Provided by publisher.
Includes bibliographical references (pages 321-336) and index.
Keywords: Historic preservation -- Planning; Historic buildings -- Conservation and restoration -- Planning; Historic sites -- Conservation and restoration -- Planning; Cultural property -- Protection -- Planning; Cultural policy